2016
DOI: 10.1007/s11105-016-0995-x
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genetic Diversity in Sweet Cassava Cultivars from Paraná, Brazil

Abstract: The objectives of the present study were to assess the population structure and genetic diversity in traditional sweet cassava cultivars collected in Bbackyard^cultivations in the municipalities of Maringá, Cianorte, and Toledo, State of Paraná, Southern Brazil, using 13 SSR molecular markers. All the loci analyzed were considered polymorphic with a mean of 3.15 alleles per locus; the mean polymorphism information content (PIC) value found was 0.4598, indicating that the primers were reasonably informative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 52 publications
5
23
0
Order By: Relevance
“…Our results show the presence of 17 rare alleles with frequency values ranging from 0.0096 to 0.0306, corroborating with previously published data Peroni et al, 2007;Rocha et al, 2008;Siqueira et al, 2009;Asare et al, 2011;Turyiagienda et al, 2012;Costa et al, 2013;Ferreira et al, 2015;Ortiz et al, 2016).…”
Section: Genetic Diversity Indicessupporting
confidence: 93%
See 4 more Smart Citations
“…Our results show the presence of 17 rare alleles with frequency values ranging from 0.0096 to 0.0306, corroborating with previously published data Peroni et al, 2007;Rocha et al, 2008;Siqueira et al, 2009;Asare et al, 2011;Turyiagienda et al, 2012;Costa et al, 2013;Ferreira et al, 2015;Ortiz et al, 2016).…”
Section: Genetic Diversity Indicessupporting
confidence: 93%
“…The mean PIC value found was low compared to others studies related to cassava reported in the literature (Xia et al, 2005;Asare et al, 2011;Turyagyenda et al, 2012). On the other hand, studies developed by Costa et al (2013) and Ortiz et al (2016) with traditional sweet cassava cultivars from Paraná State, Brazil, showed PIC values such as 0.4040 and 0.4598. This fact can be explained because smaller and more homogeneous populations tend to present lower values of informative content per locus.…”
Section: Genetic Diversity Indicesmentioning
confidence: 89%
See 3 more Smart Citations